2019
DOI: 10.5708/ejmh.14.2019.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualization Of Negative Attitudestowards People with Schizophrenia in Turkey

Abstract: Previous studies have shown that stigmatizing attitudes toward individuals with schizophrenia are common in Turkey, and Turkish society has a tendency to reject such individuals. The purpose of this paper, therefore, is to provide an overview of negative attitudes towards people with schizophrenia in Turkey. A systematic search of the literature in Academic Search Complete, CINAHL, ERIC, MEDLINE, and PsycINFO was performed to review these negative attitudes. Six major themes were identified in 32 studies: (a) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…In Türkiye, attitudes towards mental disorders, especially schizophrenia, tend to carry negative characteristics, and individuals can be stigmatized due to their illnesses [22]. In a study with nursing students in Türkiye, it was stated that 22.9% of students perceived mental disorders as "desperation," and 28.3% saw it as an "uncontrollable condition or damaging element" [23].…”
Section: Discussionmentioning
confidence: 99%
“…In Türkiye, attitudes towards mental disorders, especially schizophrenia, tend to carry negative characteristics, and individuals can be stigmatized due to their illnesses [22]. In a study with nursing students in Türkiye, it was stated that 22.9% of students perceived mental disorders as "desperation," and 28.3% saw it as an "uncontrollable condition or damaging element" [23].…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, mental health professionals included in the study were the ones who presented the most stigmatizing beliefs toward people with the disorder. In Turkey, a systematic search of the national literature showed that healthcare providers, caregivers and families, the public and students had negative attitudes toward people with schizophrenia ( 35 ). Additionally, stigma also contaminates the pre-clinical stages of psychosis, as further evidence drawn from a systematic review showed that there is also stigma associated with the CHR label ( 36 ).…”
Section: Discussionmentioning
confidence: 99%